Detection of bacterial agents associated with appendicitis At Al-Nassyriah city - Hassan, Mohammed (University of Thi-Qar Journal of Science, 2015)
The present study was include examination of the content of 100 surgical removed appendices for identify thebacteria found in flamed appendix cavity. The study recorded infection percentage by intestinal bacteria reached 83%, fecalith 6% and body foreign 2%. The results showed that the single infection percentage was 77% included infection of Esherichia coli, Bacteroides sp, Pseudomonas sp, Lactobacillus sp, Staphylococcus auerus, Salmonella sp, Proteus sp, Klebsiella sp and Yersinia sp by percentages (33%, 15%, 11%, 7%. 4%, 2%, 2%, 2%, 1%) respectively. Dual infection percentage (6%) included infection of Esherichia coli+ Bacteroides sp, Esherichia coli+ Salmonella sp, Pseudomonas sp+ Lactobacillus sp by percentages were (3%, 2%, 1%) respectively.